Consumption of coffee and tea with add-ins in relation to daily energy, sugar, and fat intake in US adults, 2001–2012. (May 2017) - An, R.; Shi, Y.
Highlights: Coffee and tea are among the most widely consumed beverages in US adults. Many people prefer drinking coffee and tea with caloric add-ins like sugar or cream. We examined the nutritional implications of coffee/tea intake with caloric add-ins. Drinking coffee/tea with caloric add-ins noticeably increased daily energy intake. The incremental energy intake predominantly came from sugar and total/saturated fat.